CATALYTIC CONVERTER BERBAHAN GIPSUM DENGAN CAMPURAN SERBUK TEMBAGA TERHADAP EMISI GAS BUANG - Trisna Aditya; Abdul Ghofur (Universitas Lambung Mangkurat, 2019)
The purpose of this study is to find out the use of Gypsum-based Catalytic Converter and a mixture of Copper Powder Against Exhaust Gas Emissions and Engine Performance. This study uses an experimental method, the population in this study was Suzuki Satria FU motorcycle in 2009, the data of this study were numbers that showed the exhaust gas content of CO, HC. This research was carried out in the Banjarmasin environment office using a gas analyzer and was also carried out in the Banjarmasin plug and play workshop by using a dynamometer. The technique used in data collection was the variation in rpm and number of compositions. From experiments with three different compositions, the following results were obtained: (1) The results of this study are: the form of Catalytic Converter with composition C, the level of HC emission reduction is maximum of 78,91%, the level of CO emission reduction is 82,96%. The form of Catalytic Converter with plate variation 6 (six), the maximum level of CO2 emission reduction is 29,56%, the level of CO emission reduction is 49,32%, and the level of HC emission reduction is 82,92%. (2) Using a Catalytic Converter produces a power of 10,29 Hp and a Torque of 10,35 Nm. Keywords: Catalytic Converter, Emission, Gypsum, Muffler, Concentration